Ta’sir al Khalfiyah al Ta’limiyah Lil Walidain ‘ala Dafi’iyah Ta’lim al Lughah al ‘Arabiyah li Thalibat Bi Ma’had Wali Songo Lil Banat Cukir Jombang - kamaliyafatikhi, izan; Isniyatun Niswah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
Apart from the Islamic boarding schools friendship environment which has a big impact on children’s growth,parents educational backround is one of the main factors in children’s development to influence their motivation to leanrn Arabic.as an activity that has educational objectives,it becomes a means of developing a persons qualities and thoughts in life.this research uses quantitative research methods with a statistical analysis approach and descriptive analysis research types as well as inferential analysis,data collection techniques in the from of observation,questionnaires or questionnaires and documentation,data analysis techniques in the from of quantitative descriptive statistical analysis techniques,simple regression analysis,hypothesis testing and then conclusions.therefore the results of the analysis obtained are t count = 1639 and t table = 1,671 so that the t count must be smaller than the t table and the p-value = 0,107 is greater of 0,05 or H0 is acceted.